Kinetic models of peroxidase activity in potato leaves infected with late blight based on hyperspectral data - Li, Qingyu; Hu, Yaohua (International Journal of Agricultural and Biological Engineering, 2019)
Potato late blight, which is caused by Phytophthorainfestans (Mont.) de Bary, is a worldwide devastating disease for potato. It decreased yields of potato and caused unpredictable losses all over the world. Various simple statistical methods and forecasting models have been developed to predict and manage potato late blight. Meanwhile, there is a rising need to develop prediction models reflecting peroxidase (POD) activity, which is an important health index that varies with infection and correlated with stress resistance in plants. Thus, the aim of this research was to develop kinetic models to predict POD activity. Infection-induced changes in potato leaves stored in an artificial climate chest at 25°C were analyzed using hyperspectroscopy. Four prediction models were developed by using linear partial least squares (PLS) and nonlinear support vector machine (SVM) methods based on the full spectrum and effective wavelengths. The effective wavelengths were selected by the successive projection algorithm (SPA). In this study, the prediction model developed by means of SPA-SVM method obtained the best performance, with a Rp (correlation coefficient of prediction) value of 0.923 and a RMSEp (root mean square error of prediction) value of 24.326. Five-order kinetics models according to the prediction model were developed, and late blight disease can be predicted using this model. This study provided a theoretical basis for the prediction of latencies of late blight. Keywords: POD (peroxidase) activity, kinetic model, potato leaves, late blight, hyperspectral data, latency prediction DOI: 10.25165/j.ijabe.20191202.4574 Citation: Li Q Y, Hu Y H. Kinetic models of peroxidase activity in potato leaves infected with late blight based on hyperspectral data. Int J Agric & Biol Eng, 2019; 12(2): 160–165.